Tworząc kreatywne zajęcia popkulturowe dla młodzieży: intencje – doświadczenia – refleksje - Prósinowski , Piotr (Studia Edukacyjne, 2021)
Pop culture has its significant place in education. It is also a space within which social processes take place and experiences, beliefs and cultural archetypes are presented and discussed. This text is a kind of revisiting of thoughts collected during workshops for young people focusing on various creative processes, particularly writing texts, expression through words and body, introducing elements of theatrical exercises, discussions of popular culture and everyday experiences of workshop participants. The purpose of the text is not just to offer conclusions and reflections after conducting such workshops, but also to critically look at processes like socialization, education and upbringing.